2018
DOI: 10.3389/fmicb.2018.02516
|View full text |Cite
|
Sign up to set email alerts
|

Equine Methicillin-Resistant Sequence Type 398 Staphylococcus aureus (MRSA) Harbor Mobile Genetic Elements Promoting Host Adaptation

Abstract: Continuing introduction of multi-drug resistant, zoonotic pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) in horse clinics challenges the biosafety of employees and animal patients. This study was aimed to determine the occurrence of mobile genetic elements facilitating survival in the early stages of invasive infection in different host species, including humans and horses, in MRSA carried by equine patients admitted to a large horse clinic. A total of 341 equine patients were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 53 publications
0
37
0
2
Order By: Relevance
“…Haemolysin is a chief virulence factor of many Vibrio and other bacteria (Syed et al, ; Walther et al., ). Tan, Liu, Oliver, and Wong () suggested that haemolysin is regulated by the rpoS gene and expressed in cells under low salinity in Vibrio vulnificus .…”
Section: Discussionmentioning
confidence: 99%
“…Haemolysin is a chief virulence factor of many Vibrio and other bacteria (Syed et al, ; Walther et al., ). Tan, Liu, Oliver, and Wong () suggested that haemolysin is regulated by the rpoS gene and expressed in cells under low salinity in Vibrio vulnificus .…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) is among the leading causes of opportunistic infectious diseases in human and veterinary medicine worldwide 1 , 2 . Mobile genetic elements (MGEs) originally denominated as staphylococcal cassette chromosome mec (SCC mec ) cause horizontal spread of methicillin resistance among staphylococci 3 , with either mec A or mec C 4 , 5 as the resistance-mediating gene.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms enabling opportunistic bacteria to cross species barriers, to infect a new host or to enhance their viability in the environment are still poorly understood. Changes expected to be involved in (niche) adaptation processes of S. aureus encompass (among others) alterations of metabolic pathways 17 , escape of host defence mechanisms 1 , biofilm formation 18 , iron acquisition abilities 19 , generation of pseudogenes 20 , 21 or nucleotide changes altering promoter structures 22 . In addition, production of cytotoxins 23 , 24 and other virulence factors as well as their regulation circuits might have a strong influence on host adaptation 23 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations